2019
DOI: 10.1186/s13046-019-1068-4
|View full text |Cite
|
Sign up to set email alerts
|

DRAM2 acts as an oncogene in non-small cell lung cancer and suppresses the expression of p53

Abstract: BackgroundDamage-regulated autophagy modulator 2(DRAM2) is associated with autophagy processes. However, the role of DRAM2 in the progression of human neoplasms is still unknown. Here, we show that DRAM2 may act as an oncogenic regulator in non-small cell lung cancer (NSCLC).MethodsTumor specimens from 259 NSCLC patients were collected and analyzed. Transwell migration, cell cycle analysis, MTT and colony formation assays were performed to determine the effect of DRAM2 overexpression and knockdown on NSCLC-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 27 publications
(25 reference statements)
0
17
0
Order By: Relevance
“…14 DRAM2 was found serve as an oncogene in non-small cell lung cancer and retinoblastoma. 15,16 We showed overexpression of DRAM2 stimulates GC cell growth by inhibiting cell apoptosis and facilitating cell cycle, and could reverse the roles of sh-KCNQ1OT1 on GC cell behaviors. There is limitation in this work which is we did not recruit GC patients into our work so that we are unable to validate expression level of the triplet network and their corrections in GC tissues.…”
Section: Discussionmentioning
confidence: 95%
“…14 DRAM2 was found serve as an oncogene in non-small cell lung cancer and retinoblastoma. 15,16 We showed overexpression of DRAM2 stimulates GC cell growth by inhibiting cell apoptosis and facilitating cell cycle, and could reverse the roles of sh-KCNQ1OT1 on GC cell behaviors. There is limitation in this work which is we did not recruit GC patients into our work so that we are unable to validate expression level of the triplet network and their corrections in GC tissues.…”
Section: Discussionmentioning
confidence: 95%
“…DRAM2 (MIM 613360) encodes a DNA-damage regulated autophagy modulator 2 (DRAM2), also known as transmembrane protein 77 (TMEM77), a 266 amino acid transmembrane protein containing six putative transmembrane domains [6,7]. It is ubiquitously expressed in numerous tissues, including the lymph nodes, spleen, heart, and placenta [8,9], where it localizes to lysosomal membranes and is thought to play a role in the autophagy process and tumor suppression [6,7,10,11]. Immunohistochemical analysis of the retina revealed that DRAM2 localizes to the inner segments of the photoreceptors and the apical surface of the RPE cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…Higher expression levels of DRAM2 in NSCLC are associated with TNM stage and lymph node metastasis. As an oncogene, interference with DRAM2 can induce upregulation of p53 and p21 expression in NSCLC cells ( 89 ). Quercetin, a chemical extracted from a traditional Chinese drug, has been shown to promote HDGF secretion and to induce autophagy.…”
Section: The Role Of Pcd In the Metastasis Of Nsclcmentioning
confidence: 99%